Antidepressants and the risk of psoriasis induction: A case–control study - Seyedeh-Fatemeh Sadatmadani; Amir Hossein Siadat; Fariba Iraji; Fereshteh Alsahebfosoul (Advanced Biomedical Research, 2023)
Background: Psoriasis (PSO) is a common chronic autoimmune skin disease with a significant psycho-socio-economic burden. Some antidepressants (ADs) such as fluoxetine and bupropion can induce or exacerbate PSO. This study aimed to investigate the correlation between ADs history before PSO onset, and the risk of PSO induction, in Isfahan province, Iran. Materials and Methods: In this case–control study, 80 patients with PSO were selected by non-probability sampling method, and 80 healthy individuals were selected using simple random sampling. They were interviewed and medical information was recorded. Chi-square, Mann–Whitney, and Kruskal–Wallis tests for dichotomous or categorical data, and independent-sample t test for continuous data were used. Statistical significance was taken as P ≤ 0.05. Results: In this case–control study, a total of 160 individuals, 80 participants in each group, were included. The mean age of the total samples was 44.8 ± 16 years. Forty-three percent of the individuals were women. PSO familial history in the cases was significantly higher than the control group (OR = 11.94, P = 0.001). It was revealed that use of ADs by patients before PSO induction, was greater than the controls (OR = 2.78, P = 0.058). Conclusions: Past history of ADs in the cases before PSO onset, was higher than the controls, indicating a possible association between ADs and the risk of PSO induction. This study can be effective to pay more attention to the possible complications of ADs and PSO risk factors. Accurate knowledge of PSO risk factors will be useful for better management and morbidity reduction.